2019
DOI: 10.1136/vetreco-2017-000264
|View full text |Cite
|
Sign up to set email alerts
|

Randomised clinical trial showing the curative effect of bandaging on M2‐stage lesions of digital dermatitis in dairy cows

Abstract: Objectives and designThis trial evaluated the effect of bandaging of acute painful ulcerative bovine digital dermatitis (DD) lesion (stage M2) in dairy cows, tested using two different topical treatments.DesignRandomised clinical trial.SettingThis study was conducted using Holstein-Friesian cows ranging in age from heifers to fourth lactation in a single dairy herd and diagnosed with acute ulcerative DD lesions (stage M2) on the first examination (week 0). Cows were randomly assigned into either a non-bandaged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 33 publications
0
21
0
Order By: Relevance
“…This is a relapsing and remitting disease, and our aim, here, was proof-of-principle rather than a clinical trial but it convincingly demonstrated that the barrier is easily applied, is robust and well tolerated, locks in a pre-applied therapeutic and allows lesions to heal. Whether this will turn out to be a superior method for dealing with digital dermatitis, compared to current state-of-art management, would require a controlled trial with larger numbers but it is worth noting that Klawitter et al 3 , cite an urgent requirement for new approaches to bandaging in this disease and we believe that the materials presented here have that potential. Liquid bandages were prepared by the sequential mixing of (a) metal salts (copper, zinc and/or iron), (b) additives (e.g.…”
Section: Discussionmentioning
confidence: 89%
“…This is a relapsing and remitting disease, and our aim, here, was proof-of-principle rather than a clinical trial but it convincingly demonstrated that the barrier is easily applied, is robust and well tolerated, locks in a pre-applied therapeutic and allows lesions to heal. Whether this will turn out to be a superior method for dealing with digital dermatitis, compared to current state-of-art management, would require a controlled trial with larger numbers but it is worth noting that Klawitter et al 3 , cite an urgent requirement for new approaches to bandaging in this disease and we believe that the materials presented here have that potential. Liquid bandages were prepared by the sequential mixing of (a) metal salts (copper, zinc and/or iron), (b) additives (e.g.…”
Section: Discussionmentioning
confidence: 89%
“…The use of bandaging in DD lesion healing has not been widely studied as a treatment option due to the extra time and costs involved in applying the bandage compared to footbaths or a simple spray method. In a study in Germany, the use of bandaging was tested to see if it accelerated the healing of DD lesions with both an antibiotic and non-antibiotic; the results showed that by bandaging the lesion, no matter the treatment option, it helped increase the rate of healing [11]. This suggested that there was an advantage to using a bandage for treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In these cases a rigorous surgical debridement in combination with an antibiotic spray (chlortetracycline), a block on the sound claw and a bandage led to 72.7% healing rate after 28 days ( Kofler et al., 2015 ). Bandaging enhances the efficacy of treatment for Treponema related diseases because it promotes a prolonged exposure to treatment ( Klawitter et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Protecting the exposed corium from mechanical irritation and slurry may prove beneficial for healing of SU ( J. K. Shearer, Plummer & Schleining, 2015 ). Bandaging has been shown to be effective in healing other claw diseases by prolonging the exposure of treatment to the lesion ( Klawitter, Döpfer, Braden, Amene & Mueller, 2019 ). A review, however, by Potterton et al.…”
Section: Introductionmentioning
confidence: 99%